English Slang Words Used On 2022 Tiktok Platform - Dhelvia, Dheva; Maca, Sudirman; Asyrafunnisa, Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2024)
This objective of the research were to find out the types of slang word that used on tiktok platform and to find out the positive impacts and negative impacts of the used of slang word on tiktok platform. The writer used qualitative descriptive method and used Allan and Burridge’s theory to find out the types of slang word that use on tiktok platform. The positive and negative impacts of  the used of slang words on the tiktok platform analyzed by the comment section of the videos. There are 5 types of the slang word used by content creator on tiktok platform, they are fresh and creative, flippant, imitative, acronym, and clipping. The result of this research shows fresh and creative is the most frequently used for english slang word. There are comments of tiktok users shows positive words and negative words. The result of data collected shows that tiktok users provide more positive impacts from comments than negative impacts.